1991
DOI: 10.1093/jpepsy/16.2.137
|View full text |Cite
|
Sign up to set email alerts
|

The Impact of Maternal Perceptions and Medical Severity on the Adjustment of Children with Congenital Heart Disease

Abstract: Hypothesized that maternal perceptions would be more significant predictors of emotional adjustment than medical severity. Mothers of 99 children, between the ages 4-10 years, completed the Child Behavior Checklist, Parenting Stress Index, Parental Locus of Control Scale, and a measure of perception of medical severity. Assessed medical severity by number of hospitalizations, operations, catheterizations, hospital days, outpatient visits, and a cardiologist's rating of illness severity. Maternal perceptions we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

9
100
1
2

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 165 publications
(112 citation statements)
references
References 0 publications
9
100
1
2
Order By: Relevance
“…The first group included mothers of children with moderate to severe CHD, recruited through a large pediatric cardiology clinic at a children's hospital. Cardiac severity was rated by each child's pediatric cardiologist using the Cardiologist's Perception of Medical Severity (DeMaso, et al, 1991), which has a rating scale ranging from 1 = insignificant (disorder has no impact on child's health) to 5 = severe (uncorrectable lesion or only complex, palliative repair possible), and an inter-rater reliability of .97. Five pediatric cardiologists participated in this study.…”
Section: Methodsologymentioning
confidence: 99%
“…The first group included mothers of children with moderate to severe CHD, recruited through a large pediatric cardiology clinic at a children's hospital. Cardiac severity was rated by each child's pediatric cardiologist using the Cardiologist's Perception of Medical Severity (DeMaso, et al, 1991), which has a rating scale ranging from 1 = insignificant (disorder has no impact on child's health) to 5 = severe (uncorrectable lesion or only complex, palliative repair possible), and an inter-rater reliability of .97. Five pediatric cardiologists participated in this study.…”
Section: Methodsologymentioning
confidence: 99%
“…109,110,112 The responses to these exercise questionnaires reflect children's and families' experiences of living with congenital heart defects: the limitations that they report will be influenced by what they are physically able to do and also by what they believe that they can do. 113 Most children with congenital heart defects seem to regain good exercise capacity after operation, although a minority will have complex disease or further complications, such as pulmonary hypertension or heart failure, which severely limit activity. Some manifestations of specific congenital heart defects, for example, cyanosis, are associated in general with greater limitations on exercise.…”
Section: Exercise Capacity and Daily Functioningmentioning
confidence: 99%
“…(2) Rather, parents' perception of the impact of their child's CHD on the child and family has proven to be a far more powerful predictor of long-term psychological morbidity. (50) Although parents of children with CHD and DS tended to experience higher levels of stress over the time-span of the study, no significant association was found between the presence of DS and levels of parenting stress. The lack of association may be a reflection of the fact that parents viewed their children as either having a medical problem, or not, irrespective of the number of problems.…”
Section: Discussionmentioning
confidence: 81%